ANALYSIS OF FERTILIZER PURCHASING DECISIONS FOR PALM OIL FARMERS ON THE INFLUENCE OF TYPE, QUANTITY AND PRICE OF FERTILIZER IN PARDAMEAN LABUHANBATU REGENCY - Zulfida, Ida; Lindawati, L (Agros Journal of Agriculture Science, 2024)
The aim of this research is to find out how much influence the type of fertilizer, quantity and price of fertilizer has on the decision to purchase fertilizer among oil palm farmers in Perdamean Dalam Village, Rantau Selatan District, Labuhanbatu Regency. In this research, the sample used was 83 oil palm farmers. The data analysis method in this research is quantitative descriptive. The results of this research show that the type of fertilizer, quantity and price of fertilizer have a positive and significant effect on the decision to purchase fertilizer among oil palm farmers in Perdamean Village, Rantau Selatan District, Labuhanbatu Regency, while the type of fertilizer has a positive and but not significant effect on the decision to purchase fertilizer. Based on the results of simultaneous tests, the variables of fertilizer type, quantity and price of fertilizer influence purchasing decisions. Keywords: Fertilizer Type, Price, Purchasing Decision.